2021
DOI: 10.1101/2021.10.27.466093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Qualitative and quantitative top-down proteomics of human colorectal cancer cell lines identified 23000 proteoforms and revealed drastic proteoform-level differences between metastatic and non-metastatic cancer cells

Abstract: Understanding cancer metastasis at the proteoform level is crucial for discovering new protein biomarkers for cancer diagnosis and drug development. Proteins are the primary effectors of function in biology and proteoforms from the same gene can have drastically different biological functions. Here, we present the first qualitative and quantitative top-down proteomics (TDP) study of a pair of isogenic human metastatic and non-metastatic colorectal cancer (CRC) cell lines (SW480 and SW620). This study pursues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Two top-down MS/MS data sets were used in this study: one public RPLC−MS/MS data 42 (MASSIVE: MSV000080257) and one CZE-MS/MS data. 6 The RPLC−MS/MS data set was generated from ovarian tumor samples. A solid-phase extraction column (360 μm o.d.…”
Section: Top-down Ms Data Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two top-down MS/MS data sets were used in this study: one public RPLC−MS/MS data 42 (MASSIVE: MSV000080257) and one CZE-MS/MS data. 6 The RPLC−MS/MS data set was generated from ovarian tumor samples. A solid-phase extraction column (360 μm o.d.…”
Section: Top-down Ms Data Setsmentioning
confidence: 99%
“…The CZE-MS/MS data sets were obtained from SW480 and SW620 colon cancer cells. 6 Sample proteins were first separated by an SEC column into six fractions, and then each fraction was injected into a linear polyacrylamide-coated fused silica capillary (1 m, 50 μm i.d., 360 μm o.d.) with 5% acetic acid as the background electrolyte.…”
Section: Top-down Ms Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in high resolution and high accuracy MS instruments significantly increased proteoform identifications and amino acid sequence converge in proteome-wide top-down proteomics analysis [4]. Recent top-down MS studies identified more than 23,000 proteoforms from colorectal cancer cells [5] and about 30,000 proteoforms from human blood and bone marrow cells [6]. Top-down MS-based proteoform profiling has successfully identified differentially expressed proteoforms associated with diseases [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%